Lupus Nephritis With Mild Asymptomatic Hypercalcemia in Children: A Case Report and Literature Review - Xu, Lingling; Zhang, Jun; Pu, Ronghui; Yue, Zhihui; Mo, Ying; Jiang, Xiaoyun (Frontiers in Pediatrics, 2019)
Lupus nephritis (LN) in Children is caused by Kidney involvement in systemic lupus erythematosus (SLE). SLE is a chronic, multi-systemic, paroxysmal autoimmune disease with a wide spectrum of autoantibodies. Hypercalcemia is a common manifestation of primary hyperparathyroidism and other malignant tumors. LN or SLE with hypercalcemia is rare. We report a case of LN with hypercalcemia and review the literature.It suggests that the pathogenesis of SLE complicated with hypercalcemia complicates the response of drug therapy.